Independensi Auditor, Tekanan Anggaran Waktu Dan Kualitas Audit: Peran Moderasi Komitmen Organisasi Pada Kap Di Kepulauan Riau - Ita Mustika; Khadijah Khadijah; Benni Sumarman; Syifa Fauziah; Nishfu Nurbayanti (Owner : Riset dan Jurnal Akuntansi, 2025)
This study aims to examine the effect of auditor independence and time budget pressure on audit quality with organizational commitment as a moderating variable. This research was conducted at a Public Accounting Firm in the Riau Islands. The sample in this study amounted to 120 respondents. This research is a quantitative study with data analysis techniques using SEM PLS with testing of the measurement model, validity test, reliability and then testing the structural model (inner model). The results of the study indicate that auditor independence has a significant positive effect on audit quality. The more independent the auditor in carrying out his duties, the higher the resulting audit quality. Time budget pressure has a significant negative effect on audit quality. Organizational commitment is able to moderate the effect of time budget pressure on audit quality. Auditors with a high level of organizational commitment maintain audit quality despite facing time pressure, while organizational commitment does not moderate the effect of auditor independence on audit quality. Auditor independence still has a positive impact on audit quality, regardless of the level of organizational commitment. This research has a novelty by presenting the organizational commitment variable as a moderating factor in the Indonesian context, especially at KAP in the Riau Islands which is still rarely explored in the literature. Practically, the results of this study can be valuable input for the auditor profession in improving audit quality through strengthening organizational commitment amidst the challenges of independence and time budget pressure.